Comparison of mini-percutaneous nephrolithotomy by standard and miniperc instruments in pediatric population: A single-center experience - Abhay Dinkar Mahajan (Wolters Kluwer Medknow Publications, 2021)
Objective: The objective of this study was to compare mini-percutaneous nephrolithotomy (PCNL) performed by standard and Miniperc techniques in pediatric patients. Materials and Methods: This was a retrospective study conducted at our institution between January 2012 and December 2017. The outcomes of pediatric renal stones treated by mini-PCNL done by Miniperc and standard techniques were compared in terms of the drop in the hemoglobin, stone-free rate, and analgesic requirement in the first 24 h. Results: A total of 57 children (age: 1–16 years), who underwent mini-PCNL by Miniperc equipment (n = 23) and standard equipment (n = 34), were included in this study. The postoperative mean drop in hemoglobin was significantly higher in mini-PCNL done by standard compared to the Miniperc technique. The stone-free rate was 95.65% in the Miniperc group and 94.12% in the standard mini-PCNL group. The need for analgesics was significantly lower in the Miniperc group compared to the standard mini-PCNL group (P = 0.0002). In the Miniperc group, the majority of the patients required only one dose of analgesics, whereas, in the standard mini-PCNL group, around 44% of the patients required three or more than three doses of analgesics to reduce postoperative pain. Conclusion: Both the techniques were safe and efficacious in the management of pediatric renal stone and stone clearance. However, the Miniperc technique resulted in significantly less pain and a lower dosage of analgesics.